2020
DOI: 10.7717/peerj.8411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial diversity and abundance between sexes of Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) from China

Abstract: Background Insects harbor a myriad of microorganisms, many of which can affect the sex ratio and manipulate the reproduction of the host. Leptocybe invasa is an invasive pest that causes serious damage to eucalyptus plantations, and the thelytokous parthenogenesis, low temperature resistance, protection in galls, generation overlap and small body of L. invasa contribute to its rapid invasion and population growth. However, the endosymbiotic bacterial composition, abundance and sex differences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…The Bacteroidia Flavobacterium helps digesting plant material by producing cellulase in three phytophagous insect species [ 52 ] while Sphingobacterium induces resistance against fungal infection in Delia antiqua larvae [ 66 ]. Although the α-proteobacterial ANPR or Rhizobium is usually known as a nitrogen-fixing bacterium living in symbiosis with legume roots [ 67 ], it has also been detected in insects [ 68 ], where a gene associated to nitrogen fixation was revealed in ants that host Rhizobiales [ 69 ]. The γ-proteobacterial Acinetobacter improves both its host nutrition and defense by scavenging nitrogen [ 70 ], producing cellulase [ 52 ], and resisting and degrading plant defenses, respectively in D. radicum [ 53 ] and in the gypsy moth [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bacteroidia Flavobacterium helps digesting plant material by producing cellulase in three phytophagous insect species [ 52 ] while Sphingobacterium induces resistance against fungal infection in Delia antiqua larvae [ 66 ]. Although the α-proteobacterial ANPR or Rhizobium is usually known as a nitrogen-fixing bacterium living in symbiosis with legume roots [ 67 ], it has also been detected in insects [ 68 ], where a gene associated to nitrogen fixation was revealed in ants that host Rhizobiales [ 69 ]. The γ-proteobacterial Acinetobacter improves both its host nutrition and defense by scavenging nitrogen [ 70 ], producing cellulase [ 52 ], and resisting and degrading plant defenses, respectively in D. radicum [ 53 ] and in the gypsy moth [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…While sex is often not considered when studying insect microbial communities, there is evidence of differences in microbiota composition between females and males in Leptocybe invasa (Guo et al, 2020), Dendroctonus valens (Xu et al, 2016), Anopheles gambiae and Anopheles coluzzii (Segata et al, 2016).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%
“…Previous studies confirmed that females pass Rickettsia to the next generation using vertical transmission (Brumin et al, 2012;Giorgini et al, 2010). Himler et al (2011) showed that the rate of Rickettsia to offspring was close to 100% by female vertical transmission, and the same phenomenon may also be reflected in L. invasa (Guo et al, 2020;Nugnes et al, 2015). Remarkably, some studies have demonstrated the presence of horizontal transmission of Rickettsia, although transmission was mainly achieved by mating or feeding on the same host plants (Brumin et al, 2012;Caspi-Fluger et al, 2012).…”
Section: Composition Of the Bacteriamentioning
confidence: 84%
“…Rickettsia (Guo et al, 2020), while no available evidence could prove the phenomenon of horizontal transmission in L. invasa (Gualtieri et al, 2017) which will be our study of the next stage.…”
Section: Composition Of the Bacteriamentioning
confidence: 94%